Cross-Talk Between Alveolar Macrophages and Lung Epithelial Cells is Essential to Maintain Lung Homeostasis - Bissonnette, Elyse Y.; Lauzon-Joset, Jean-François; Debley, Jason S.; Ziegler, Steven F. (Frontiers in Immunology, 2020)
The main function of the lung is to perform gas exchange while maintaining lung homeostasis despite environmental pathogenic and non-pathogenic elements contained in inhaled air. Resident cells must keep lung homeostasis and eliminate pathogens by inducing protective immune response and silently remove innocuous particles. Which lung cell type is crucial for this function is still subject to debate, with reports favoring either alveolar macrophages (AMs) or lung epithelial cells (ECs) including airway and alveolar ECs. AMs are the main immune cells in the lung in steady-state and their function is mainly to dampen inflammatory responses. In addition, they phagocytose inhaled particles and apoptotic cells and can initiate and resolve inflammatory responses to pathogens. Although AMs release a plethora of mediators that modulate immune responses, ECs also play an essential role as they are more than just a physical barrier. They produce anti-microbial peptides and can secrete a variety of mediators that can modulate immune responses and AM functions. Furthermore, ECs can maintain AMs in a quiescent state by expressing anti-inflammatory membrane proteins such as CD200. Thus, AMs and ECs are both very important to maintain lung homeostasis and have to coordinate their action to protect the organism against infection. Thus, AMs and lung ECs communicate with each other using different mechanisms including mediators, membrane glycoproteins and their receptors, gap junction channels, and extracellular vesicles. This review will revisit characteristics and functions of AMs and lung ECs as well as different communication mechanisms these cells utilize to maintain lung immune balance and response to pathogens. A better understanding of the cross-talk between AMs and lung ECs may help develop new therapeutic strategies for lung pathogenesis.